POTENTIAL EVAPOTRANSPIRATION TREND ANALYSIS FOR DIFFERENT CLIMATIC ZONES IN KHYBER PAKHTUNKHWA, PAKISTAN - Nazeer, M. (The Nucleus, 2012)
Estimation of potential evapotranspiration (ETo) plays a significant role in the study of water resources management. The study was conducted to investigate the change in potential evapotranspiration value during the past three decade in three diverse climatic zones of Khyber Pakhtunkhwa, Pakistan. Three Districts of Khyber Pakhtunkhwa, Pakistan (Chitral, Peshawar and D. I. Khan) were selected based on their climatic diversity. Thirty years climatic data (1981- 2010) obtained from Pakistan Metrological Department, Islamabad and Agriculture Research Institute, Peshawar was used. Potential evapotranspiration was determined for three decades separately, as well as on mean monthly basis. World Meteorological Organization (WMO) technique was used for trend analysis. Results revealed highest ETo in D.I Khan followed by Peshawar and Chitral. However, in the summer months ETo value was found highest in Chitral as compared to other selected Districts. Trend analysis results showed that decrease in ETo trend was observed in all the selected Districts with the passage of time. It can be concluded that ETo values decreased as compared to past in all the selected Districts without any discrimination of physical geography and location.